Pengaruh Pengenceran Nanokoloid Perak Hasil Biosintesis Menggunakan Ekstrak Tanaman Keladi Sarawak(Alocasia macrorrhizos (L.)) Sebagai Bahan Aktif Gel Melawan Staphylococcus aureus - Athiah Masykuroh; Patrisia Aprilia; Nabila Rizka Ananda (Jurnal Komunitas Farmasi Nasional, 2025)
The study on evaluate the effect of dilution concentration of silver nanocolloids synthesized using Alocasia macrorrhizos (L.)) extract as the active ingredient in gel formulations on their antibacterial activity against Staphylococcus aureus has been conducted. The gel with undiluted nanocolloid was compared with the previous formulation containing 50% diluted nanocolloid. The gel was formulated using a Carbopol 940 base and evaluated for organoleptic properties, pH, homogeneity, viscosity, spreadability, and hedonic acceptance. Antibacterial activity was assessed using the disk diffusion method. The results showed that the gel met all physical parameters except viscosity. The antibacterial activity against Staphylococcus aureus was categorized as strong, with inhibition zones of 11.52 ± 0.10 mm (F1), 11.83 ± 0.19 mm (F2), and 12.44 ± 0.65 mm (F3). Increasing the nanocolloid concentration from 50% to 100% did not produce a significant difference in antibacterial activity.